Creating Partnerships for Capacity Building in Developing Countries : The Experience of the World Bank - McCarthy, F. Desmond (World Bank, Washington, DC, 2014)
The authors discuss a variety of experiences in a number of transition, and developing countries to build institutional capacity for economics education. A flexible approach met with some success. The approach uses partnerships that combine the often different needs of a number of private donors, with the World Bank on the supply side. Much of the success was due to adopting each effort to the individual country situation. The authors also provide a brief summary of five academic institutions, and four research networks in Europe, Africa, Asia, and Latin America.